BOARD ATTRIBUTES AND SUSTAINABILITY REPORTING OF LISTED FIRMS IN NIGERIA - Idris Mohammed; Bejamin K. Gugong; Rofiat Adedokun; Abdulrahman A. Olorunloga; Mark G Tagwai (Gusau Journal of Accounting and Finance)
This study investigates the impact of board attributes on sustainability reporting among listed firms in Nigeria from 2013 to 2022, using a correlational research design. The research population encompasses all Nigerian listed firms, with a stratified sampling technique deemed appropriate for the study. Secondary data were sourced from the audited annual reports and accounts of sampled firms available on the Nigerian Exchange Group (NGX) website. The analysis of the extracted panel data was conducted using multiple regression techniques with STATA version 13. The findings of the study reveal that board size, gender diversity, and independence positively influence sustainability reporting, while board commitment has a negative impact on sustainability reporting. Consequently, the study recommends that the management of Nigerian listed firms should view large and diverse boards as an asset for promoting sustainability reporting. Such boards, comprising experienced and knowledgeable members, are more likely to make effective decisions on sustainability-related issues. Additionally, the presence of women on boards should be considered a valuable factor in encouraging comprehensive financial reporting, which includes qualitative and quantitative information on the social, environmental, and economic activities of the business for stakeholders.